1988
DOI: 10.1080/00365518809085757
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the trabecular component to mechanical strength and bone mineral content of the femoral neck. An experimental study on cadaver bones

Abstract: Both proximal femora from 10 females were acquired at autopsy. The trabecular component of the femoral neck of one specimen from each pair was evacuated, while the contralateral specimen was left intact as a reference. Bone mineral content (BMC) of the femoral neck, demonstrated only a slight (mean 4.8%) individual side to side variation. After evacuation of the trabecular component, BMC was reduced with mean 23.5%. Mechanical strength of the specimens, determined by applying a force to the femoral head perpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Recently, Ferretti et al (1995) have suggested a ''paradigm shift'' away from the traditional view of osteoporosis as a cancellous bone disease, arguing that agerelated fractures begin in the epiphyseal and metaphyseal cortices, rather than the spongiosa. Experimental evidence (Martens et al, 1983;Werner et al, 1988) and finite element models (Lotz et al, 1995) support these contentions and indicate that the cortex carries a substantial portion of the load in the proximal femur, although the contribution of the metaphyseal cortical shell is strongly dependent upon the applied loading conditions (Pinilla et al, 1996). In spite of this, relatively few studies have examined age-related changes in the microstructure or morphology of the metaphyseal cortex in the proximal human femur.…”
mentioning
confidence: 73%
“…Recently, Ferretti et al (1995) have suggested a ''paradigm shift'' away from the traditional view of osteoporosis as a cancellous bone disease, arguing that agerelated fractures begin in the epiphyseal and metaphyseal cortices, rather than the spongiosa. Experimental evidence (Martens et al, 1983;Werner et al, 1988) and finite element models (Lotz et al, 1995) support these contentions and indicate that the cortex carries a substantial portion of the load in the proximal femur, although the contribution of the metaphyseal cortical shell is strongly dependent upon the applied loading conditions (Pinilla et al, 1996). In spite of this, relatively few studies have examined age-related changes in the microstructure or morphology of the metaphyseal cortex in the proximal human femur.…”
mentioning
confidence: 73%
“…Some authors have attributed the exponential increase in hip fracture risk with aging to thinning of the cortex of the neck, (24,25) whereas others suggest a synergistic action and a decline in both cortical and trabecular bone. (26)(27)(28) Mechanical testing of excised femoral necks also has given variable results, ranging from cortical contributions of 40% to 60% (14,26) to almost 100% (29) for overall femoral strength. Similarly, finite-element modeling (FEM) has suggested that in the femoral neck region, cortical bone supports 50% of the stresses associated with normal gait or during a fall on the side.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the effect of cancellous bone loss, the role of cortical bone in hip fractures has been recently examined. Both experimental evidence (Werner et al, 1988) and finite element analysis (Lotz et al, 1995) have suggested that the cortex of the femoral neck carries a substantial portion of the load, and thus age-related changes in the morphology and microstructure of the cortex may be a significant contributing factor in hip fractures.…”
mentioning
confidence: 99%